Podiel osobnostných a interpersonálnych činiteľov na vysvetlení sociálnej pohody učiteľov. / The share of personal and interpersonal factors in explaining social well-being of teachers. - Anna Janovská, Oľga Orosová (Czech Pedagogical Society, 2013)
The aim of the presented study was to establish the share of personality variables and social support from school headteachers in explaining variance of social well-being of teachers. We utilized the concept of social well-being as stated by Keyes (1998). The questionnaire IASR-B5 (Trapnell & Wiggins, 1990) was used todetect personality traits and The Brief Resilience Scale (Smith et al., 2008) to detect the level of resilience. Providing of social support was measured by the SAS-C scale (Trobst, 2000) based on circumplex model of interpersonal behaviour, describing eight types of supportive behaviour. The research sample consisted of 256 primary school teachers. The results were processed by multivariate linear regression analysis. Regression models confirmed a significant share of supportive behaviour of schoolheadteachers in explaining variance of social well-being variables.